Case Report: Superficial Circumflex Iliac Artery Perforator Flap for Tongue Reconstruction Following the Hemiglossectomy - Fang, Yihong; Ouyang, Qiming; Zheng, Zhi; Wang, Jin (Frontiers in Surgery, 2021)
Objective: Therapeutic evaluation of applying superficial circumflex iliac artery perforator (SCIP) flap in tongue reconstruction after hemiglossectomy. Methods: We retrospectively collected a total number of fourteen patients who received SCIP flap reconstruction for tongue defects at the Fujian Medical University affiliated Union Hospital, between November 2016 and November 2020. We evaluated the clinical features of the flap, analyzed the postoperative functions and esthetic effects after 6 months of the tongue reconstruction. Results: All the SCIP flaps survived successfully after the operation, the recipient site tongue bodies were well reconstructed 6 months after the surgery. Patient speech and swallowing functions were well recovered during the follow-up. The scars in the donor site were concealed with limited numbness. Conclusions: With the advantages of the hidden donor site and aesthetic benefits, the SCIP flap is a reliable option for reconstruction of the tongue defect after hemiglossectomy.